2023
DOI: 10.3390/cells12152005
|View full text |Cite
|
Sign up to set email alerts
|

StemRegenin-1 Attenuates Endothelial Progenitor Cell Senescence by Regulating the AhR Pathway-Mediated CYP1A1 and ROS Generation

Abstract: Endothelial progenitor cell (EPC)-based stem cell therapy is a promising therapeutic strategy for vascular diseases. However, continuous in vitro expansion for clinical studies induces the loss of EPC functionality due to aging. In this study, we investigated the effects of StemRegenin-1 (SR-1), an antagonist of aryl hydrocarbon receptor (AhR), on replicative senescence in EPCs. We found that SR-1 maintained the expression of EPC surface markers, including stem cell markers, such as CD34, c-Kit, and CXCR4. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Various studies [71,72] show that natural products and phytochemicals may exert their chemopreventive effects by inducing or inhibiting CYP1A1 expression. Studies have shown that the increase in CYP1A1 expression induces ROS formation [73][74][75][76][77]. Thus, the reduction in CYP1A1 expression by DATS in the CoTx premalignant cells may explain the attenuation of ROS production observed in this study.…”
Section: Discussionsupporting
confidence: 61%
“…Various studies [71,72] show that natural products and phytochemicals may exert their chemopreventive effects by inducing or inhibiting CYP1A1 expression. Studies have shown that the increase in CYP1A1 expression induces ROS formation [73][74][75][76][77]. Thus, the reduction in CYP1A1 expression by DATS in the CoTx premalignant cells may explain the attenuation of ROS production observed in this study.…”
Section: Discussionsupporting
confidence: 61%
“… 19 It has also been reported that SR1 can promote the terminal differentiation of human erythroblasts and attenuates endothelial progenitor cell senescence by inhibiting AhR signaling. 20 , 21 Recent studies have shown that the expression of the AhR pathway is associated with bone loss in mice, but various studies have contradicted each other and the specific mechanism of action has not been clarified. 22 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%